Effectiveness of Ultrasound-Guided Regional Anaesthesia in Paediatric Patients Undergoing Urological Surgeries: A Systematic Review: Ultrasound-Guided Regional Anaesthesia in Paediatric Patients Undergoing Urological Surgeries - Ahmad, Shabir; Hassan, Hafiz Wajih Ul; Akram, Saba; Zaidi, Syed Imtiaz Ali; Ahmed, Aftab; Shafiq, Pakeeza; Shah, Muhammad Arsalan (Pakistan Journal of Health Sciences, 2024)
Recent research in anatomy and ultrasound has highlighted the importance of a technique named ultrasound-guided regional anaesthesia in pediatric anaesthesia, due to its approach to enhancing nerve visualization and targeted nerve blockade which improves patients’ safety and pain relief during surgical procedures. Objectives: To evaluate the outcomes of pediatric patients who received ultrasound-guided regional anaesthesia during urological surgeries and compare its effectiveness in pain control, anaesthetic quality, and post-surgery results. Methods: A search was conducted according to PRISMA guidelines using PubMed, Google Scholar, Springer Link, and Science Direct. A total of 96 studies were included after applying the inclusion criteria to articles published between January 2013 and April 2024. Out of these, only 15 were used in the study table to highlight the effectiveness of ultrasound-guided regional anaesthesia in pediatric urological surgeries. Results: Consistently, the alignment with the ultrasound-guided regional anaesthesia revealed significantly greater analgesic efficacy, least opioid usage as well and lesser rates of anaesthesia-related adverse events in pediatric subjects mainly neurodevelopmental concerns and opioid dependency. Other papers also revealed better hemodynamic control and the duration of time needed to feel fully recovered postoperatively, and thus, ultrasound-guided regional anesthesia may enhance perioperative outcomes and ambience in children undergoing different urological procedures. Conclusions: It was concluded that ultrasound-guided regional anaesthesia appears to be applicable for pediatric urological surgery, providing better analgesia, fewer side effects, and reduced demand for systemic anaesthesia. Future studies should establish the long-term results of the method and make comparisons to the other procedures